2018
DOI: 10.1371/journal.pone.0195013
|View full text |Cite
|
Sign up to set email alerts
|

The urine albumin-creatinine ratio is a predictor for incident long-term care in a general population

Abstract: BackgroundSeveral types of cardiovascular diseases (CVDs) impair the physical and mental status. The purpose of this study was to assess the predictive ability of several cardiovascular biomarkers for identifying the incidence of disability as future recipients of public long-term care (LTC) service.MethodsThe subjects of this study were community-dwelling elderly individuals ≥ 65 years of age without a history of CVD (n = 5,755; mean age, 71 years). The endpoint of this study was official certification as a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
6
0
1
Order By: Relevance
“…An elevated level of the urinary albumin to creatinine ratio (UACR) is not only a marker of renal dysfunction but also has been described as an independent predictor of cardiovascular disease in diabetic [1, 2] and non-diabetic patients [3, 4]. Moreover, recent findings have indicated that the UACR is more closely associated with diabetic retinopathy than the estimated glomerular filtration rate (eGFR) [5] and might be valuable in evaluating the risk for cognitive decline [6, 7]. Additionally, a robust body of literature has demonstrated that moderately increased albuminuria (UACR less than 30 mg/g) within the accepted normal range is associated with higher cardiovascular morbidity and mortality even in the general population [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…An elevated level of the urinary albumin to creatinine ratio (UACR) is not only a marker of renal dysfunction but also has been described as an independent predictor of cardiovascular disease in diabetic [1, 2] and non-diabetic patients [3, 4]. Moreover, recent findings have indicated that the UACR is more closely associated with diabetic retinopathy than the estimated glomerular filtration rate (eGFR) [5] and might be valuable in evaluating the risk for cognitive decline [6, 7]. Additionally, a robust body of literature has demonstrated that moderately increased albuminuria (UACR less than 30 mg/g) within the accepted normal range is associated with higher cardiovascular morbidity and mortality even in the general population [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…High IL-6 plasma levels are associated with functional impairment in elderly individuals with vascular dementia [55]. A previous study showed that albuminuria predicted future functional disability [29]. Given these findings, poor SRH might be an alternative index of functional disability with physical impairment and cognitive dysfunction caused by asymptomatic brain infarction or endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Body mass index was calculated as body weight [kg] divided by the square of height [m]. Blood pressure, anthropometric data, results of blood tests (serum levels of total cholesterol (TC; mg/dl), high-density lipoprotein cholesterol (HDLC; mg/dl), non-high-density lipoprotein cholesterol (non-HDLC; mg/dl), hemoglobin (Hb; g/dl), and glycosylated hemoglobin (HbA1c; %)), and estimated glomerular filtration rate (eGFR; mL/min/1.73 m 2 ) were used for analysis [ 24 , 29 ]. Participants answered a self-reported questionnaire that was prepared by the study committee.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations